2020
DOI: 10.1038/s41598-020-63627-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbial metabolite stercobilin involvement in the chronic inflammation of ob/ob mice

Abstract: It is crucial that the host and intestinal microflora interact and influence each other to maintain homeostasis and trigger pathological processes. Recent studies have shown that transplantation of the murine intestinal content to recipient germ-free mice enables transmission of the donor's phenotypes, such as low level chronic inflammation associated with lifestyle-related diseases. These findings indicate that intestinal bacteria produce some molecules to trigger pathological signals. However, fecal microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The residues were dissolved in 50% MeOH (50 μL) and subjected to LC-MS, consisting of an ACQUITY Ultraperformance liquid chromatography (UPLC) (Waters, Milford, MA) coupled with a micrOTOF-Q II (Bruker Daltonics, Bremen, Germany). UPLC separation was performed with an Ethylene Bridged Hybrid (BEH) C18 column (1.7 μm, 50 mm × 2.1 mm i.d., Waters) at 40 °C, using solvent A (0.1% formic acid in water) and solvent B (MeCN containing 0.1% formic acid). Samples were eluted from the column using a linear gradient starting at 1% solvent B (0 min) to 99% solvent B at 10–12 min.…”
Section: Methodsmentioning
confidence: 99%
“…The residues were dissolved in 50% MeOH (50 μL) and subjected to LC-MS, consisting of an ACQUITY Ultraperformance liquid chromatography (UPLC) (Waters, Milford, MA) coupled with a micrOTOF-Q II (Bruker Daltonics, Bremen, Germany). UPLC separation was performed with an Ethylene Bridged Hybrid (BEH) C18 column (1.7 μm, 50 mm × 2.1 mm i.d., Waters) at 40 °C, using solvent A (0.1% formic acid in water) and solvent B (MeCN containing 0.1% formic acid). Samples were eluted from the column using a linear gradient starting at 1% solvent B (0 min) to 99% solvent B at 10–12 min.…”
Section: Methodsmentioning
confidence: 99%
“…Stercobilinogen is oxidized to stercobilin, which is responsible for the pigmentation of feces. The microbial metabolites urobilinogen, urobilin, stercobilinogen, and stercobilin that are formed by intestinal bacteria play a main role in liver diseases [51].…”
Section: Discussionmentioning
confidence: 99%
“…Cholic acid may accelerate the development of atherosclerosis by activating oxidative stress-induced macrophage mobilization signals [ 47 ]. Stercobilin, a pigment in feces, was formed by intestinal bacteria, which could induce proinflammatory activities in mice [ 48 ]. These results indicated that capsaicin administration could significantly change the cecal metabolomic profile of ApoE −/− mice and prevent the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%